Met and Hgf signaling controls hypaxial muscle and lateral line development in the zebrafish - Haines, Lynn; Neyt, Christine; Gautier, Philippe; Keenan, David G; Bryson-Richardson, Robert J; Hollway, Georgina E; Cole, Nicolas J; Currie, Peter D (Development (Cambridge), 2004)
Somites give rise to a number of different embryonic cell types, including the precursors of skeletal muscle populations. The lateral aspect of amniote and fish somites have been shown to give rise specifically to hypaxial muscle, including the appendicular muscle that populates fins and limbs. We have investigated the morphogenetic basis for formation of specific hypaxial muscles within the zebrafish embryo and larvae. Transplantation experiments have revealed a developmentally precocious commitment of cells derived from pectoral fin level somites to forming hypaxial and specifically appendicular muscle. The fate of transplanted somites cannot be over-ridden by local inductive signals, suggesting that somitic tissue may be fixed at an early point in their developmental history to produce appendicular muscle. We further show that this restriction in competence is mirrored at the molecular level, with the exclusive expression of the receptor tyrosine kinase met within somitic regions fated to give rise to appendicular muscle. Loss-of-function experiments reveal that Met and its ligand, hepatocyte growth factor, are required for the correct morphogenesis of the hypaxial muscles in which met is expressed. Furthermore, we demonstrate a requirement for Met signaling in the process of proneuromast deposition from the posterior lateral line primordia.